Spinal tuberculosis: imaging features on MRI - Simmi Bhatnagar; Ambry Garg; Amarjit Kaur; Navkiran Kaur; Jaswinder Mohi (International Journal of Medical Research and Review, 2018)
Introduction: Spine is the most common site of skeletal tuberculosis.Radiographic manifestations of tuberculous spondylitis include intraosseous and paraspinal abscess formation, subligamentous spread of infection, vertebral body destruction and collapse, and extension into the spinal epidural space. Significant instability and deformity of the spine can result, mandating prompt diagnosis and treatment to prevent permanent neurologic damage.Objective: This is a prospective and descriptive study to evaluate the role of MRI in spinal tuberculosis and various spectrum ofits manifestations.Materials and Methods: This prospective study was on 25 patients of either age or sex with clinical suspicion of spinal TB over a period of 2 years and subsequently went MR Imaging and features were correlated with other investigations and histopathological diagnosis in few patients.Results: Thoracic spine was the most common site of involvement.Vertebral body wedge collapse or compression fracture was seen in 64 % of patients. Posterior element involvement was found in 10 out of 25 cases. Prevertebral & paravertebral collections were seen in88% of cases. Epidural soft tissue component was seen in 56% of cases.Conclusion: MRI is the best diagnostic modality for spinal TB and to demonstratethe various associated manifestations which help in assessing the extent and severity of the disease and thus inearly and correct management planning.